Whose Inflation? : A Characterization of the CPI Plutocratic Bias - Ley, Eduardo (IMF Working Papers; Working Paper ;, 2001)
Prais (1958) showed that the CPI computed by statistical agencies can be interpreted as a weighed average of household price indexes, the weight of each household determined by its total expenditures. We decompose the difference between the standard CPI and a democratically weighed index (i.e., the plutocratic bias) as the product of average income, income inequality, and the covariance between individual price indexes and a parameter related to each good's income elasticity. This decomposition allows us to interpret variations in the size and sign of the plutocratic bias, and also to discuss issues pertaining to group indexes.